Study of Knowledge, Attitude, and Practices of Use of Masks among Health-care Workers at a Tertiary Care Center in Mumbai - Sharan Sadashiva Kadamba; Kalpana Tikaram Suryavanshi; Khushi P. Bhatia (Journal of Advanced Lung Health)
Introduction: Airborne transmission of infectious diseases poses a significant public health challenge. Nosocomial outbreaks of airborne infections such as influenza H1N1, H5N1, and drug-resistant tuberculosis (TB) variants have been documented, with substantial morbidity and mortality attributed to inadequate airborne infection control strategies. N-95 respirators and surgical masks (face masks) are the examples of personal protective equipment that are used to protect the wearer from airborne particles and liquid contamination of the face. Aim and Objectives: The aim of this study was to assess the knowledge, practices, and attitude of health-care workers (HCWs) regarding the use of mask, especially N-95 mask. Materials and Methods: A prospective, was conducted over a period of 6 months at a tertiary care hospital. This study was carried out in the department of microbiology of a tertiary care hospital over a period of 6 months. A total of 500 HCWs from various departments of the hospital were included in the study. HCWs were given a questionnaire based on N-95 respirator usage, and participation was voluntary. Results: The analysis of survey data provides insightful perspectives on respondents’ comprehension and attitudes toward airborne infection transmission and the usage of N-95 masks. 68.6% of respondents recognized that all listed diseases (measles, TB, and chickenpox) were spread by the airborne route. 55.6% of respondents correctly acknowledged that all masks, including surgical masks, N-95 masks, and cotton masks, do not offer airborne protection. 76.0% of respondents acknowledged that N-95 masks possess a high filtration efficiency against 0.3-micron particles, 58.3% correctly identified that “N” in N-95 stands for “not resistant to oil,” and 90.8% acknowledged that the N-95 respirator as the most common type of respirators. 41.7% correctly acknowledged that N-95 masks with an exhalation valve are not recommended for use. 22.2% of respondents incorrectly believe that wearing a face mask can lead to carbon dioxide poisoning, and 52.1% of respondents correctly identified that pulmonary TB patients need not be provided with N-95 masks in isolation rooms. 76.8% of respondents understood that fit testing is required every time one dons an N-95 mask. 95.5% of respondents recognized the necessity of hand hygiene before donning and after doffing N-95 masks. 82.7% of respondents agreed regarding the necessity for consultation before N-95 mask usage for chronic lung disease and asthma patients. 93.7% are aware that there is a protocol for donning and doffing N-95 masks. 71.3% of respondents understood that extended use involves wearing the same N-95 respirator for repeated close contact encounters without removing the mask between patient encounters, while 64.4% correctly define reuse as using the same N-95 respirator for multiple encounters but removing it after each encounter.